2016
DOI: 10.1371/journal.pone.0162390
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 Fimbriae Encoded on Plasmids Are Expressed from a Unique Promoter without Affecting Host Motility, Facilitating an Exceptional Phenotype That Enhances Conjugal Plasmid Transfer

Abstract: Horizontal gene transfer (HGT), the transmission of genetic material to a recipient that is not the progeny of the donor, is fundamental in bacterial evolution. HGT is often mediated by mobile genetic elements such as conjugative plasmids, which may be in conflict with the chromosomal elements of the genome because they are independent replicons that may petition their own evolutionary strategy. Here we study differences between type 3 fimbriae encoded on wild type plasmids and in chromosomes. Using known and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…An enhanced plasmid transfer might provide plasmids the opportunity to establish themselves in new hosts, triggering different evolutionary processes and increasing the capacity to occupy new ecological niches. As a result, a host-plasmid combination, including potential pathogens carrying plasmids that harbor antibiotic resistance genes, can persist in the long term (Madsen et al, 2016;Zhang et al, 2014), in particular when microplastics are present. Considering that plastic pollution in aquatic systems is increasing and may soon surpass the total fish biomass in the ocean (World Economic Forum and Ellen MacArthur Foundation, 2017), further studies on their colonization by bacteria and subsequent transfer of genetic elements are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced plasmid transfer might provide plasmids the opportunity to establish themselves in new hosts, triggering different evolutionary processes and increasing the capacity to occupy new ecological niches. As a result, a host-plasmid combination, including potential pathogens carrying plasmids that harbor antibiotic resistance genes, can persist in the long term (Madsen et al, 2016;Zhang et al, 2014), in particular when microplastics are present. Considering that plastic pollution in aquatic systems is increasing and may soon surpass the total fish biomass in the ocean (World Economic Forum and Ellen MacArthur Foundation, 2017), further studies on their colonization by bacteria and subsequent transfer of genetic elements are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…These so-called CRISPR interference (CRISPRi) systems, silence the expression of targeted genes by blocking transcription factor binding or RNA polymerase elongation 58 . Moreover, type IV-mediated gene silencing could serve purposes beyond plasmid-plasmid warfare, such as altering host expression profiles to enhance plasmid propagation and/or stabilise maintenance, all piracy practices which plasmids are known to invoke via diverse mechanisms 59,60,61 . In the context of CRISPRi functionality, for which R-loop formation between the crRNA and the DNA target is key, the common association of DinG with type IV loci appears paradoxical, as it is well documented that the substrate for this helicase are R-loops that block replication fork advancement 62,63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…As the above indicated that active only-GGDEF and only-EAL CDSs were common on plasmid replicons, we theorized that DGCs and PDEs may be positively selected for on transmissible plasmids because these enzymes may induce biofilm and motile phenotypes, respectively, both of which have been shown to enhance rates of conjugative plasmid transfer [8]. We, therefore, characterized the plasmids as transmissible or non-transmissible based on the presence or absence of relaxase DCSs, respectively [9].…”
mentioning
confidence: 99%
“…We, therefore, speculated that some plasmids may promote specific host behaviors to enhance their own transfer frequency. To this end, the biofilm phenotype was of specific interest as it can promote conjugative plasmid transfer [8,13]. To test this, we performed the following proof-ofconcept experiments: we obtained a conjugative wild-type plasmid, pUUH239.2 [14], harbored by Klebsiella pneumoniae, which encodes a DGC.…”
mentioning
confidence: 99%